Lighting in High Definition from the seventh season of the Televisión Española soap opera Amar en tiempos revueltos (2020)
This article discusses the way in which lighting professionals articulate the expressive possibilities of light to support the Spanish production of television fiction series in high definition: How they distribute the light to adapt it to the narrative needs of the scene and the technical requirements of the television cameras. The case study chosen is the seventh season of Amar en tiempos revueltos, produced by Diagonal TV for Televisión Española, since it is one of the most successful series of Spanish television, and it exceeds the rest of national broadcast television soap operas regarding number of chapters. The theoretical foundation deficit led to in-depth interviews with directors of photography and lighting directors in these television productions. For the treatment of the data obtained (through the dialogic technique and the direct viewing of the fiction episodes), the qualitative methodology of the analysis of content was used. This approach gives a central character to the text, in this case audiovisual, and is used to measure the frequency and significance of the selected elements. Among the most significant conclusions of the research, it can be noted that the lighting in high definition of the seventh season of Amar en tiempos revueltos differentiates the environments of the diegesis, despite carrying a rhythm of production that exceeds a chapter per day. In addition, the methodology is likely to become a reference framework for future research, and for possible revisions and discussions in academia.